Electrochemically controlled cocrystallisation of caffeine:1-hydroxy-2-naphthoic acid - Kaliszczak, M.; Durand, P.; Wenger, E.; Dossot, M.; Jones, Franca; Arrigan, Damien; Herzog, G. (ROYAL SOC CHEMISTRY, 2022)
Controlled formation of cocrystals is an important objective in drug development. Here, cocrystallisation of caffeine and 1-hydroxy-2-naphthoic acid was investigated at the interface between two immiscible electrolyte solutions under chemical polarisation. In this way, selective cocrystallisation was achieved, as verified by X-ray diffraction and Raman spectroscopy. Positive interfacial potentials favoured the formation of one polymorphic form of caffeine:1-hydroxy-2-naphthoic acid cocrystal. This approach to electrochemically controlled cocrystallisation opens up new possibilities for drug development.